PEWAHYUAN AL-QUR’AN; MENELUSURI HISTORIS TURUNNYA AL-QUR’AN - Sari, Dian; Nasrullah Bin Sapa (Amsal Al-Qur’an: Jurnal Al-Qur’an dan Hadis, 2025)
The Qur'an is a holy book in which there are words (revelations) of Allah, which were conveyed by the angel Gabriel to the Prophet Muhammad صَلَّى اللهُ عَلَيْهِ وَسَلَّمَ as the apostle of Allah in stages, which aims to be a guide for Muslims in their lives and lives. to obtain prosperity in this world and the hereafter. Nuzulul Quran is interpreted as the event where the Al-Quran was revealed as well as the time when the Prophet Muhammad صَلَّى اللهُ عَلَيْهِ وَسَلَّمَ was inaugurated as a Prophet and Messenger by Allah SWT. The Qur'an was revealed to have a function as a miracle, as a guide to life for every Muslim, as a corrector of previous books, keeper of previous books (Al-Muhaimin), judge of what is disputed by humans, and abolish the Shari'a of the books previous. The Qur'an also has other names such as Al-Kitab, Al-Huda, Al-Furqan, Ar-rahmah- Ar-ruh, Ash-syifa, Al-Haq, Al-Mauizhah and Al-Bayan, Adz-Dzikru, and An-Nur.